Manejo integrado de insectos plagas en el cultivo de zanahorias (Daucus carota L.) - Avilés Campos, Miguel Alfredo (2022)
This document details the main pests that affect carrot crops, in order to refer to the topic on "Integrated management of insect pests in carrot crops (Daucus carota L.)", the information collected was subjected to processes of citation with IICA-CATIE standards, of textual citations where the integrated management of pests in carrot cultivation was discussed. In addition, it was determined that the main insect pests that attack carrot crops are Aphids (Cavariella aegopodii, Aphis spp., Myzus persicae); Carrot fly (Psylla rosae), Gray Worms (Agrotis sp) and Wire Worms (Agriotes sp), devouring the roots and causing them to rot, which leads to reduced yields and in turn influences the economic income of the farmers. farmers and the best control methods are linked to each other, combining cultural, etiological, chemical and biological control, where it can be detailed that crop rotation is used as cultural control; etiological control with yellow traps; chemical control chlorpyrifos at a dose of 300 cc / ha, biological control applying Beauveria bassiana and Metharhizium anisopliae.